2005
DOI: 10.1016/j.mod.2005.03.008
|View full text |Cite
|
Sign up to set email alerts
|

E-cadherin is required for gastrulation cell movements in zebrafish

Abstract: E-cadherin is a member of the classical cadherin family and is known to be involved in cell-cell adhesion and the adhesion-dependent morphogenesis of various tissues. We isolated a zebrafish mutant (cdh1(rk3)) that has a mutation in the e-cadherin/cdh1 gene. The mutation rk3 is a hypomorphic allele, and the homozygous mutant embryos displayed variable phenotypes in gastrulation and tissue morphogenesis. The most severely affected embryos displayed epiboly delay, decreased convergence and extension movements, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
151
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(169 citation statements)
references
References 51 publications
11
151
1
Order By: Relevance
“…When E-cadherin adhesion is disrupted during Zebrafish epiboly, epiblasts still intercalate but are not stabilized in the external layer and often deintercalate (Kane et al 2005;Shimizu et al 2005). Intercalation during gastrulation involves remodeling of AJs to expand cell-cell adhesions in one plane of the epithelium and contract them in the perpendicular plane (Bertet et al 2004).…”
Section: Roles Of Classical Cadherins In Dynamic Cell Movementsmentioning
confidence: 99%
“…When E-cadherin adhesion is disrupted during Zebrafish epiboly, epiblasts still intercalate but are not stabilized in the external layer and often deintercalate (Kane et al 2005;Shimizu et al 2005). Intercalation during gastrulation involves remodeling of AJs to expand cell-cell adhesions in one plane of the epithelium and contract them in the perpendicular plane (Bertet et al 2004).…”
Section: Roles Of Classical Cadherins In Dynamic Cell Movementsmentioning
confidence: 99%
“…These studies showed that merely changing the expression level of a single adhesion system can result in markedly altered sorting behavior (Duguay et al, 2003;Foty and Steinberg, 2005). In zebrafish E-cadherin mutant and morphant embryos, mesendodermal germ layer morphogenesis is initially largely unaffected (Babb and Marrs, 2004;Kane et al, 2005;Montero et al, 2005;Shimizu et al, 2005), indicating that E-cadherin activity is not critical for mesendodermal progenitor cell ingression and early migration. The key difference between our in vitro experiments and the situation in E-cadherin mutant and morphant embryos is that we specifically down-regulated E-cadherin expression in one of the two germ layer tissues, whereas in the mutant and morphant embryos E-cadherin expression of both germ layers was equally affected.…”
Section: Downregulation Of E-cadherin-based Cohesivity In the Ectodermentioning
confidence: 99%
“…The roles of cadherins in morphogenetic processes that entail enhanced cell motility are much more varied and complex, and can mediate dynamic behaviors of cells as well as stable interactions (Brieher and Gumbiner, 1994;Chihara et al, 2003;Geisbrecht and Montell, 2002;Matsunaga et al, 1988;Medioni et al, 2008;Pollack et al, 1998;Shimizu et al, 2005). Moreover, a loss of the expression of one cadherin during an EMT or similar morphogenetic process is often associated with the increased expression of a different cadherin.…”
Section: Introductionmentioning
confidence: 99%